Comparison of Six Different Percutaneous Coronary Intervention Guidance Modalities - Mengjin Hu; Jiangshan Tan; Yuejin Yang (Journal of Cardiovascular Development and Disease, 2022)
Background: New randomized trials and modalities in guiding percutaneous coronary intervention (PCI) have become available. Objective: We aimed to compare the clinical outcomes of coronary angiography (CAG), intravascular ultrasound (IVUS), optical coherence tomography (OCT), fractional flow reserve (FFR), instantaneous wave-free ratio (iFR), and optical frequency domain imaging (OFDI)-guided PCI. Methods: A network meta-analysis was performed to compare different PCI guidance modalities. The clinical outcomes included major adverse cardiovascular events (MACE), all-cause death, myocardial infarction (MI), and target vessel/lesion revascularization (TVR/TLR). Odds ratio (OR) and corresponding 95% credible interval (CrI) were calculated. Results: Thirty-six randomized trials, including 19,042 patients, were included. In comparison with CAG, IVUS significantly reduced MACE (OR: 0.71; 95% CrI: 0.57 to 0.86) and TVR/TLR (OR: 0.53; 95% CrI: 0.43 to 0.66). MACE (OR: 1.44; 95% CrI: 1.02 to 2.08) and TVR/TLR (OR: 1.87; 95% CrI: 1.04 to 3.71) were significantly increased in the FFR group, compared with IVUS group. There were no significant differences in MACE or TVR/TLR among the left guidance modality comparisons. Differences in all-cause death or MI were not observed in any comparisons. Conclusions: IVUS could reduce MACE and TVR/TLR, compared with CAG or FFR. Therefore, IVUS may be the optimal modality in guiding PCI.